Learning Methods in Q.S An-Nahl Verse 125 Based on Tafsir Al-Misbah - Asyraful Khairi; Dedi Masri; Reza Pratama; Sabina Rasmita Dalimunthe (Tinta Emas Publisher, 2023)
This research examines three teaching methods in Islamic education for a better understanding of effective learning methods. The focus is on Surah An-Nahl, verse 125, and the interpretation of Al-Misbah. Data was obtained through content analysis related to teaching methods and the interpretation of verse 125. The researcher used secondary sources of information such as books and relevant articles. Data analysis was conducted using Tafsir Ijmal to understand the essence of the Quran as a clear guide for life. The method of hikmah emphasizes fundamental understanding through knowledge and righteous actions. The method of mau'izhah requires support from experience and role modeling, but it should be avoided if incomplete. The method of jidal introduces knowledge and stimulates students' interest through variation and evaluation. Its implementation should allow for critical thinking. The verse expresses three approaches in Quranic education: hikmah, mau'izhah hasanah, and jidal. Their application requires deep knowledge, good morals, the use of appropriate words, and a proportional attitude. Education with gentle words is more effective in fostering peace.